Impact of nanomechanical resonances on lasing from electrically pumped quantum dot micropillars - Czerniuk, T.; Tepper, J.; Akimov, A. V.; Unsleber, S.; Schneider, C.; Kamp, M.; Höfling, S.; Yakovlev, D. R.; Bayer, M. (Applied Physics Letters)
We use a picosecond acoustics technique to modulate the laser output of electrically pumped GaAs/AlAs micropillar lasers with InGaAs quantum dots. The modulation of the emission wavelength takes place on the frequencies of the nanomechanical extensional and breathing (radial) modes of the micropillars. The amplitude of the modulation for various nanomechanical modes is different for every micropillar which is explained by a various elastic contact between the micropillar walls and polymer environment.

Photon-Statistics Excitation Spectroscopy of a Quantum-Dot Micropillar Laser - Kazimierczuk, T.; Schmutzler, J.; Aßmann, M.; Schneider, C.; Kamp, M.; Höfling, S.; Bayer, M. (Physical Review Letters)
We introduce photon-statistics excitation spectroscopy and exemplarily apply it to a quantum-dot micropillar laser. Both the intensity and the photon number statistics of the emission from the micropillar show a strong dependence on the photon statistics of the light used for excitation of the sample. The results under coherent and pseudothermal excitation reveal that a description of the laser properties in terms of mean input photon numbers is not sufficient. It is demonstrated that the micropillar acts as a superthermal light source when operated close to its threshold. Possible applications for important spectroscopic techniques are discussed.

Novel mechanisms of optical harmonic generation on excitons in semiconductors - Yakovlev, D. R.; Warkentin, W.; Brunne, D.; Mund, J.; Pavlov, V. V.; Rodina, A. V.; Pisarev, R. V.; Bayer, M. (Nonlinear Optics and Applications IX)

Detection of ultrasonic plate waves using ceramic strip transducers - Claes, Leander; Bause, Fabian; Rautenberg, Jens; Henning, Bernd (Proceedings SENSOR 2015)
Keywords: piezoceramics; strip transducers; plate waveguide; dispersion diagram

Inclusive Beliefs and Self-Efficacy Concerning Inclusive Education Among German Teacher Trainees and Student Teachers - Scheer, David; Scholz, Markus; Rank, Astrid; Donie, Christian (Journal of Cognitive Education and Psychology)

„Alle außer Aaron...“ – Fallbezogene Selbstwirksamkeitserwartungen, Einstellungen und Überzeugungen zukünftiger Lehrkräfte im Kontext Inklusion - Scheer, David; Scholz, Markus; Rank, Astrid; Donie, Christian (Zeitschrift für Heilpädagogik)

Measurement and Analysis of oﬀshore fog occurrences - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 95th AMS Annual Meeting)

Messtechnisches Prinzip eines neuen Einstrahlungsmessgerätes - Bendfeld, Jörg; Balluff, Stefan; Bermpohl, Wolfgang (Wissenschaftliche Verhandlungen 2015 der Deutschen Physikalischen Gesellschaft)

Performance of MERRA Data in Oﬀshore Wind Energy Applications - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the DEWEK 2015)

Advanced Integration of Oﬀshore Wind Energy into the Grid System by Power to Gas - Bendfeld, Jörg; Bouyraaman, Yassin; Balluff, Stefan; Krauter, Stefan (Proceedings of the DEWEK 2015)

Comparison of micro inverters based on practical analysis - Sadati, A.M.; Krauter, Stefan; Bendfeld, Jörg (2015 5th International Youth Conference on Energy (IYCE))

Effective large-scale PV integration: Methods to match load profile with actual PV output - Krauter, Stefan (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC))

Assessment of renewable energy resources in cameroon and special regards on energy supply - Pendieu Kwaye, M.; Bendfeld, Jörg; Anglani, N. (2015 5th International Youth Conference on Energy (IYCE))

Assessment of renewable energy resources and the use of hydro power for fluctuation compensation in Cameroon - Pendieu Kwaye, M.; Bendfeld, Jörg; Anglani, N. (2015 5th International Youth Conference on Energy (IYCE))

Cost, performance, and yield comparison of eight different micro-inverters - Krauter, Stefan; Bendfeld, Jörg (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC))

BOS cost reduction via direct PV charging of electrical vehicles - Krauter, Stefan (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC))

Stabilizing oﬀshore wind farm power feed-in via power to gas storage systems - Bendfeld, Jörg; Bouyraaman, Yassin; Balluff, Stefan; Krauter, Stefan (Proceedings of the Karlsruhe Institute of Technology (KIT) - Energy Science Technology 2015)

Discovering the potential for oﬀshore windfarms trough measurements - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the Karlsruhe Institute of Technology (KIT) - Energy Science Technology 2015)

Wind power forecasting for oﬀshore wind farms - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 10th Conference on Sustainable Development of Energy, Water and Enviroment Systems - SDEWES)

Oﬀshore wind energy development based on Merra data - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 10th Conference on Sustainable Development of Energy, Water and Enviroment Systems - SDEWES)

Oﬀshore metocean station for energy purposes - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 10th Conference on Sustainable Development of Energy, Water and Enviroment Systems - SDEWES)

Short term wind and energy prediction for oﬀshore wind farms using neural networks - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (EWEA Forecasting 2015 Technology Workshop)

A Note on Decidable Separability by Piecewise Testable Languages - Czerwinski, Wojciech; Martens, Wim; van Rooijen, Lorijn; Zeitoun, Marc (Fundamentals of Computation Theory - 20th International Symposium, (FCT) 2015, Gdańsk, Poland, August 17-19, 2015, Proceedings)

Between Authenticity and Objectification: Narrating the Self in Contemporary British Drama - Tönnies, Merle (Dramatic Minds. Performance, Cognition, and the Representation of Interiority)

Mobile Agenten in Netzwerken: Analyse von Hotspots - Stilow, Georg

Integration of Wind Energy in Power System—Modelling of a Market Oriented Energy Concept - Bouyraaman, Yassin; Bendfeld, Jörg; Breymann, Philipp; Krauter, Stefan (Renewable Energy in the Service of Mankind Vol I)

Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig

Gathering a Closed Chain of Robots on a Grid - Abshoff, Sebastian; Cord-Landwehr, Andreas; Fischer, Matthias; Jung, Daniel; Meyer auf der Heide, Friedhelm (arXiv:1510.05454)
We consider the following variant of the two dimensional gathering problem for swarms of robots: Given a swarm of $n$ indistinguishable, point shaped robots on a two dimensional grid. Initially, the robots form a closed chain on the grid and must keep this connectivity during the whole process of their gathering. Connectivity means, that neighboring robots of the chain need to be positioned at the same or neighboring points of the grid. In our model, gathering means to keep shortening the chain until the robots are located inside a $2× 2$ subgrid. Our model is completely local (no global control, no global coordinates, no compass, no global communication or vision, …). Each robot can only see its next constant number of left and right neighbors on the chain. This fixed constant is called the viewing path length. All its operations and detections are restricted to this constant number of robots. Other robots, even if located at neighboring or the same grid point cannot be detected. Only based on the relative positions of its detectable chain neighbors, a robot can decide to obtain a certain state. Based on this state and their local knowledge, the robots do local modifications to the chain by moving to neighboring grid points without breaking the chain. These modifications are performed without the knowledge whether they lead to a global progress or not. We assume the fully synchronous $\mathcal{FSYNC}$ model. For this problem, we present a gathering algorithm which needs linear time. This result generalizes the result from \cite{hopper}, where an open chain with specified distinguishable (and fixed) endpoints is considered.

Approximation and Heuristic Algorithms for Computing Backbones in Asymmetric Ad-Hoc Networks - Abu-Khzam, Faisal N.; Markarian, Christine; Meyer auf der Heide, Friedhelm; Schubert, Michael (arXiv:1510.01866)
We consider the problem of dominating set-based virtual backbone used for routing in asymmetric wireless ad-hoc networks. These networks have non-uniform transmission ranges and are modeled using the well-established disk graphs. The corresponding graph theoretic problem seeks a strongly connected dominating-absorbent set of minimum cardinality in a digraph. A subset of nodes in a digraph is a strongly connected dominating-absorbent set if the subgraph induced by these nodes is strongly connected and each node in the graph is either in the set or has both an in-neighbor and an out-neighbor in it. Distributed algorithms for this problem are of practical significance due to the dynamic nature of ad-hoc networks. We present a first distributed approximation algorithm, with a constant approximation factor and O(Diam) running time, where Diam is the diameter of the graph. Moreover we present a simple heuristic algorithm and conduct an extensive simulation study showing that our heuristic outperforms previously known approaches for the problem.

Online Top-k-Position Monitoring of Distributed Data Streams - Mäcker, Alexander; Malatyali, Manuel; Meyer auf der Heide, Friedhelm (Proceedings of the 29th International Parallel and Distributed Processing Symposium (IPDPS))
Consider n nodes connected to a single coordinator. Each node receives an individual online data stream of numbers and, at any point in time, the coordinator has to know the k nodes currently observing the largest values, for a given k between 1 and n. We design and analyze an algorithm that solves this problem while bounding the amount of messages exchanged between the nodes and the coordinator. Our algorithm employs the idea of using filters which, intuitively speaking, leads to few messages to be sent, if the new input is "similar" to the previous ones. The algorithm uses a number of messages that is on expectation by a factor of O((log Δ + k) log n) larger than that of an offline algorithm that sets filters in an optimal way, where Δ is upper bounded by the largest value observed by any node.

Discrete variational Lie group formulation of geometrically exact beam dynamics - Demoures, F.; Gay-Balmaz, F.; Leyendecker, S.; Ober-Blöbaum, S.; Ratiu, T. S.; Weinand, Y. (Numerische Mathematik)

PFC-control for improved inductor utilization - Keuck, L.; Frohleke, N.; Bocker, J.; Ziessler, A. (2015 17th European Conference on Power Electronics and Applications (EPE'15 ECCE-Europe))

Multiobjective optimal control of fluid mixing - Ober-Blöbaum, Sina; Padberg-Gehle, Kathrin (PAMM)

Relaxing mixed integer optimal control problems using a time transformation - Ringkamp, Maik; Ober-Blöbaum, Sina; Leyendecker, Sigrid (PAMM)

MIFID II Wertpapierhandel und -beratung in Veränderung - Krimphove, Dieter (Zeitschrift für das gesamte Kreditwesen (ZfgK))

Nonlinear optical sub-bandgap excitation of ZnO-based photonic resonators - Bader, Christina A.; Zeuner, Franziska; Bader, Manuel H. W.; Zentgraf, Thomas; Meier, Cedrik (Journal of Applied Physics)

Coupling Mediated Coherent Control of Localized Surface Plasmon Polaritons - Zeuner, Franziska; Muldarisnur, Mulda; Hildebrandt, Andre; Förstner, Jens; Zentgraf, Thomas (Nano Letters)
Keywords: tet_topic_plasmonics

Broadband Hybrid Holographic Multiplexing with Geometric Metasurfaces - Huang, Lingling; Mühlenbernd, Holger; Li, Xiaowei; Song, Xu; Bai, Benfeng; Wang, Yongtian; Zentgraf, Thomas (Advanced Materials)

Continuous control of the nonlinearity phase for harmonic generations - Li, Guixin; Chen, Shumei; Pholchai, Nitipat; Reineke, Bernhard; Wong, Polis Wing Han; Pun, Edwin Yue Bun; Cheah, Kok Wai; Zentgraf, Thomas; Zhang, Shuang (Nature Materials)

Metasurface holograms reaching 80% efficiency - Zheng, Guoxing; Mühlenbernd, Holger; Kenney, Mitchell; Li, Guixin; Zentgraf, Thomas; Zhang, Shuang (Nature Nanotechnology)

Symmetry exploiting control of hybrid mechanical systems - Flasskamp, Kathrin; Hage-Packhäuser, Sebastian; Ober-Blöbaum, Sina (Journal of Computational Dynamics)

High order variational integrators in the optimal control of mechanical systems - Campos, Cédric M.; Ober-Blöbaum, Sina; Trélat, Emmanuel (Discrete & Continuous Dynamical Systems - A)

A gender perspective on business process management competences offered on professional online social networks - Gorbacheva, Elena; Stein, Armin; Schmiedel, Theresa; Müller, Oliver (European Conference on Information Systems)

Potenzialbeurteilung neuer Technologien im Prozesscontrolling - vom Brocke, Jan; Müller, Oliver; Debortoli, Stefan; Reuter, Nadine (Controlling)

Self-Optimizing Organic Cache - Ahmed, Abdullah Fathi

Management and Scheduling of Accelerators for Heterogeneous High-Performance Computing - Beisel, Tobias
The use of heterogeneous computing resources, such as graphics processing units or other specialized co-processors, has become widespread in recent years because of their performance and energy efficiency advantages. Operating system approaches that are limited to optimizing CPU usage are no longer sufficient for the efficient utilization of systems that comprise diverse resource types. Enabling task preemption on these architectures and migration of tasks between different resource types at run-time is not only key to improving the performance and energy consumption but also to enabling automatic scheduling methods for heterogeneous compute nodes. This thesis proposes novel techniques for run-time management of heterogeneous resources and enabling tasks to migrate between diverse hardware. It provides fundamental work towards future operating systems by discussing implications, limitations, and chances of the heterogeneity and introducing solutions for energy- and performance-efficient run-time systems. Scheduling methods to utilize heterogeneous systems by the use of a centralized scheduler are presented that show benefits over existing approaches in varying case studies.

Evolution of Heat Flow Prediction Models for FPGA Devices - Hangmann, Hendrik

Computer Vision basierte Klassifikation von HD EMG Signalen - Haupt, Christian

Microarchitectural optimization by means of reconfigurable and evolvable cache mappings - Ho, Nam; Ahmed, Abdullah Fathi; Kaufmann, Paul; Platzner, Marco (Proc. NASA/ESA Conf. Adaptive Hardware and Systems (AHS))
Keywords: cache storage; field programmable gate arrays; multiprocessing systems; parallel architectures; reconfigurable architectures; FPGA; dynamic reconfiguration; evolvable cache mapping; many-core architecture; memory-to-cache address mapping function; microarchitectural optimization; multicore architecture; nature-inspired optimization; parallelization degrees; processor; reconfigurable cache mapping; reconfigurable computing; Field programmable gate arrays; Software; Tuning

Generator Start-up Sequences Optimization for Network Restoration Using Genetic Algorithm and Simulated Annealing - Kaufmann, Paul; Shen, Cong (Genetic and Evolutionary Computation (GECCO))